First Report of a Biting Midge Culicoides Anophelis Parasitzing Mosquito Anopheles stephensi from North-Western India - Chaudhry3, Jainder. S. Chhilar1,2*, and Sudarshan (Journal of Experimental Sciences, 2011)
Culicoides, commonly called biting midges, are haematophagus ectoparasites of insects, humans and other animals of importance to man. The present study deals with the first report and description of one such ectoparasitic ceratopogonid Culicoides (Trithicoides) anophelis Edwards which was found parasitizing on a malaria vector Anopheles (Cellia) stephensi Liston from North-western India. The parasite having an alar expanse of 2.6 mm only was identified by the standard morphotaxonomic characters such as wing-venation, tibial comb, spermatheca, mandibles and the ratio of the head, antenna and palps. This ectoparasite was found clinging to the abdomen of the host (when collected from cattle sheds) with its proboscis completely penetrating into the abdominal cavity of the host, firmly remaining in that position even during the flight of the mosquito. What was interesting in this case was the effect of its parasitization on the biology of the host. The mosquito females infested with this ectoparasite failed to lay eggs and did not survive for long even under standard insectory conditions. Based on the infestation rate of as high as 72.72% combined with a significant reduction in fecundity and mortality of the mosquito there is ample scope for this parasite as a potential source of host diminution.